Pengaruh Citra Merek, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Kosmetik Oriflame - Novitasari, Asri; Rizkiyah, Dara; Sanjaya, Vicky F. (Jurnal Manajemen Bisnis dan Keuangan, 2022)
This study aims to analyze the effect of brand image, price, and product quality on purchasing decisions on Oriflamme cosmetic products in Lampung. This research involves primary data with quantitative methods using the SmartPLS application. Primary data in the form of a questionnaire distributed online with 64 respondents through the WhatsApp application. The results of this study conclude that the brand image variable has a positive relationship to purchasing decisions but is not significant in influencing these variables, as well as the price variable on purchasing decisions. The only variable in this study that affects purchasing decisions is product quality.